Factors influencing work fatigue among gas station operators in Panaikang District - Asril, Asril; Syamsul, Muharti; Sudarman, Sumardi; Irwan, Irwan; Aswadi, Aswa (Unihealth Community Research, 2025)
Fatigue is one of the risks leading to decreased worker health, characterized by reduced energy levels when performing tasks or activities. Based on the health data from the 2023 attendance records of gas station operators in Panaikang Subdistrict, Makassar City, which included a workforce of 35 individuals, 12 employees reported frequent illness every month. For the 2024 attendance records from January to April, 9 workers experienced deteriorating health conditions, with symptoms including body pain, headaches, and stiffness in the shoulders. Of the staff, 22 (62.9%) experienced fatigue, while 13 (37.1%) did not. Research Objective: To identify the factors influencing work fatigue among gas station operators in Panaikang Subdistrict, Makassar City. Method: This study employs a quantitative research method, specifically an analytical survey design with a cross-sectional study design, to investigate the impact of length of employment, tenure, and energy intake on work fatigue among gas station operators in Panaikang Subdistrict, Makassar City. Research Results: The study indicates that there is no significant relationship between work fatigue and length of employment (p = 0.686), tenure (p = 0.458), or energy intake (p = 0.508). The findings of the study indicate that there is no substantial correlation between work fatigue and factors such as length of employment, tenure, or energy intake among gas station operators in Panaikang Subdistrict, Makassar City. Based on our findings, it can be inferred that the duration of employment, tenure, energy intake, and work fatigue do not have a significant relationship among gas station operators in Panaikang Subdistrict.